Peran Sosial Media dalam Kampanye Boikot Produk Pro Israel di Indonesia - Riyadi, Ilham; Bachtiar, Farahdiba Rahma (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2024)
Social media is the most popular communication tool in the world today, including for transnational digital activism activities. Social media helps to voice the voices of ordinary people, build awareness, and spread various ideas to various places. One of them is in the context of the Israeli-Palestinian conflict. The problems that occur in Palestine are therefore important to study. As a global phenomenon that is currently receiving attention from various parties around the world, the Palestinian issue has become a humanitarian issue. For this reason, this paper questions how non-state actors participate in building narratives and efforts to stop war and peace through social media, including in this case Indonesian Muslims. This paper uses a media approach to understand the transnational activism of the Pro-Israel Product Boycott Movement. This study found that with many Indonesians who are young people and active users of social media, the campaign has had an impact on trade and consumption of goods and services from Israeli-affiliated brands or products. Although the reaction from associations, entrepreneurs and related parties was strong enough to encourage the Indonesian government to ban the action. However, the power of civil society and institutions such as the MUI, Muhammadiyah and NU is difficult to contain in this global campaign. This is because the organization and various public figures support it. This explains that although government-level efforts have been made and have not been able to stop the attacks and protect the rights of civilians in Palestine, grassroots strategies can be an alternative to change the global situation and stop the humanitarian crisis that is happening in Palestine.